An Update on Advances in COVID-19 Laboratory Diagnosis and Testing Guidelines in India - K. S. Rajesh Kumar; Suhail Sayeed Mufti; Vinu Sarathy; Diganta Hazarika; Radheshyam Naik; Radheshyam Naik (Frontiers Media S.A., 2021)
The declaration of COVID-19 as a global pandemic has warranted the urgent need for technologies and tools to be deployed for confirming diagnosis of suspected cases. Diagnostic testing for COVID-19 is critical for understanding epidemiology, contract-tracing, case management, and to repress the transmission of the SARS-CoV-2. Currently, the Nucleic Acid Amplification Test (NAAT)-based RT-PCR technique is a gold standard test used for routine diagnosis of COVID-19 infection. While there are many commercially available RT-PCR assay kits available in the market, selection of highly sensitive, specific, and validated assays is most crucial for the accurate diagnosis of COVID-19 infection. Laboratory diagnosis of SARS-CoV-2 is extremely important in the disease and outbreak management. Development of rapid point of care tests with better sensitivity and specificity is the critical need of the hour as this will help accurate diagnosis and aid in containing the spread of SARS-CoV-2 infection. Early detection of viral infection greatly enhances implementation of specific public health intervention, such as infection control, environmental decontamination, and the closure of specific high-risk zones. Large-scale sequencing of SARS-CoV-2 genome isolated from affected populations across the world needs to be carried to monitor mutations that might affect performance of molecular tests. Creation of genome repositories and open-source genetic databases for use by global researchers is clearly the way forward to manage COVID-19 outbreak and accelerate vaccine development. This review summarizes various molecular diagnostics methods, technical guidelines, and advanced testing strategies adopted in India for laboratory diagnosis of COVID-19.